2018
DOI: 10.1021/acsomega.8b00773
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Degradation and Conservation of Historical Leather Book Covers with Macro Attenuated Total Reflection–Fourier Transform Infrared Spectroscopic Imaging

Abstract: The analytical study of historical collagen-based materials such as leather book covers is a complex task for conservation scientists. Historical leather presents a heterogeneous composition of both organic and inorganic materials that show an evident reactivity, particularly when exposed to specific environments. Its correct preservation in archival documents remains challenging as some aspects of its chemical composition, degradation, and effectiveness of conservation treatments are still not fully understoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 20 publications
0
28
0
Order By: Relevance
“…The band at 1736 cm −1 visible only in the spectrum taken on leather grain side ( Fig. 7b) could be ascribed to the presence of waxy or fatty materials, which could have been used to finish or preserve the leather [7,62]. In addition, the high intensity band at 1025 cm −1 indicates the presence of silicates from dirt adhering to the surface of leather.…”
Section: The Effect Of Hnts Dispersions On Water Dynamics In Collagenmentioning
confidence: 97%
“…The band at 1736 cm −1 visible only in the spectrum taken on leather grain side ( Fig. 7b) could be ascribed to the presence of waxy or fatty materials, which could have been used to finish or preserve the leather [7,62]. In addition, the high intensity band at 1025 cm −1 indicates the presence of silicates from dirt adhering to the surface of leather.…”
Section: The Effect Of Hnts Dispersions On Water Dynamics In Collagenmentioning
confidence: 97%
“…As a consequence, the fat saponification in the presence of Ca 2+ from carbonates can be triggered off and justifies the presence of specific infrared absorption bands due to the fatty acids' soaps. [2,34,41] Due to the importance of the lipid content in skin, we performed an NMR data processing for obtaining a semiquantitative ratio of the intensity of the peaks at 33 and 43 ppm related to the lipids and collagen signal, respectively (Table 4). For calf and goat parchment, the I 33.1 /I 43 ratio value is in the range 0.2-0.3, whereas its value T A B L E 3 13 C chemical shift with assignment from Aliev 14 for the parchment samples P-1, P-2 and P-3 14 ; see Table 3 reaches 1.7 for the sheep parchment characterised by the highest lipid content.…”
Section: Parchmentmentioning
confidence: 99%
“…Several studies have been published in the last decade reporting the application of FTIR technique to analyse tannins in historical leather. [11,[31][32][33][34] Among them, 13 C solid-state NMR spectroscopy has proven its usefulness in characterising tanning fingerprinting in vegetable tanned leather. [23] The advantage of solid-state NMR over the widely used FTIR spectroscopy lies in the fact that the signals of collagen and aromatic molecules of tannins do not overlap in the 13 C CP-MAS spectrum.…”
Section: Leathermentioning
confidence: 99%
See 1 more Smart Citation
“…3 In particular, spectroscopy has offered the opportunity for nondestructive characterization of these materials. 4,5 Thus, Raman and attenuated total reflection Fourier transform infrared (ATR–FTIR) spectroscopies have been extensively used to identify the chemical composition of selected pigments 68 on manuscripts, including ancient Egyptian papyri, through determination of the characteristic vibrational frequencies of specific molecular entities. In the specific case of ancient papyri and parchments, several studies demonstrated that black inks were mainly composed of carbon black and arabic gum, egg tempera, or beeswax as binders, 9 without any kind of added heavy metal (the introduction of these latter is normally traced to the advent of iron gall).…”
Section: Introductionmentioning
confidence: 99%